Direct synthesis of tetraalkoxysilanes from silica and alcohols. (27th February 2017) - Fukaya, Norihisa; Choi, Seong Jib; Horikoshi, Toshio; Kataoka, Sho; Endo, Akira; Kumai, Hiroshi; Hasegawa, Minoru; Sato, Kazuhiko; Choi, Jun-Chul
Abstract : A simple and efficient process for synthesizing tetraalkoxysilanes from silica and alcohols was developed using molecular sieves as dehydrating agents. Abstract : A new simple and efficient process for synthesizing tetraalkoxysilanes (TROS) directly from silica and alcohols was developed using molecular sieves as dehydrating agents. Using this method, a variety of TROS (R = ethoxy, n -propoxy, or n -butoxy) were obtained over 70% yields within 6 h. We also employed various natural silica sources in this process for practical applications.